1988
DOI: 10.1038/bjc.1988.239
|View full text |Cite
|
Sign up to set email alerts
|

c-erbB-2 expression in benign and malignant breast disease

Abstract: Summary An antibody, 21 N, raised against a synthetic peptide from the predicted sequence of the c-erbB-2 protein has been used immunocytochemically in a retrospective study of formalin fixed paraffin embedded breast biopsies. Fourteen out of 103 infiltrating ductal carcinomas exhibited positive membrane staining. Fifty-four of these tumours had lymph node involvement of which nine contained stained cells. These were all cases where the primary tumour was positive. In this series there was no correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(64 citation statements)
references
References 18 publications
(15 reference statements)
6
58
0
Order By: Relevance
“…Ovet-expression of c-erbB-2 protein, on the other hand, was strongly correlated with DFS and S in our patients. Although some earlier studies have failed to show an association between prognosis and overexpression of the c-erbB-2 protein detected by IHC (14,15,20), there is a gencral agreement among more recently published reports that overexpression of the c-erbB-2 gene product is related to poor survival in breast cancer (10)(11)(12)(13)(33)(34)(35)(36). Our results are consistent with this emerging consensus.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Ovet-expression of c-erbB-2 protein, on the other hand, was strongly correlated with DFS and S in our patients. Although some earlier studies have failed to show an association between prognosis and overexpression of the c-erbB-2 protein detected by IHC (14,15,20), there is a gencral agreement among more recently published reports that overexpression of the c-erbB-2 gene product is related to poor survival in breast cancer (10)(11)(12)(13)(33)(34)(35)(36). Our results are consistent with this emerging consensus.…”
Section: Discussionsupporting
confidence: 82%
“…Abnormalities of c-erbB-2 oncogene have been associated with the progression of several human cancers (2)(3)(4)(5). Many investigators have reported that amplification or overexpression of c-erbB-2 in breast cancer is associated with a poor prognosis (2, 3, 6-13), but, this observation has not been universally reproducible and several negative reports have also appeared in the literature (14)(15)(16)(17)(18)(19)(20)(21) Amplification of c-erbB-2 gene, overexpression of its mRNA and excess production of its protein residue are not stringently correlated with each other and overexpression of mRNA and protein can occur without c-erbB-2 gene amplification and vice versa (3,(22)(23)(24)(25)(26), This may have contributed to the conflicting findings concerning c-erbB-2 abnormality and prognosis of breast cancer since some investigators have studied DNA amplification whereas others have used protein overexpression (asscsscd by Western blot or immunohistochemistry). We now report the results of a study in which the prognostic influence of c-erbB-2 amplification analysed by dot blot hybridization and of protein overexpression assessed by immunohistochemistry (IHC) have been compared in the same group of 161 patients with brcast cancer using formalin-fixed paraffinembedded archival tissues.…”
mentioning
confidence: 95%
“…The choice of oncogenes was governed by their consistent activation in human and rodent mammary tumors. About 30%o of primary human breast cancers overexpress the c-erbB-2 protein (7,18,37,45,48 (21,44). The human c-erbB-2 gene and the rat homolog, the c-neu gene, were introduced into HCll cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, c-erbB-2 amplification has been given a greater prognostic value than most currently used prognostic factors, including hormonal receptors in positive lymph node patients (Slamon et al, 1989) and some of the immunocytochemical studies showed similar results (Gusterson et al, 1988;McCann et al, 1991). Some studies showed that c-erbB-2 overexpression was a marker of poor prognosis in N+ patients (Slamon et al, 1989;Tandon et al, 1989;Borg et al, 1990;Lipponen et al, 1993;Quenel et al, 1995), while others identified c-erbB-2 as a marker of poor prognosis in the N-subgroup of patients (Paterson et al, 1991;Press et al, 1993).…”
Section: Discussionmentioning
confidence: 90%